1998
DOI: 10.1002/(sici)1097-0290(19980520)58:4<387::aid-bit6>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Transition probability cell cycle model with product formation

Abstract: A cell cycle population model based on the transition probability model of Smith and Martin (1973) has been extended to include product synthesis and export. The model handles two probable mechanisms. In the direct production model, the product is the protein. In the transcription model, the product is the specific mRNA. The protein is synthesized by translation of the specific mRNA and subsequently exported. In either case, the cell density is jointly distributed in the primary product and maturity age in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Later, more complex formulations were reported using age and an additional intracellular property (e.g. product, RNA) [34, 35]. Similarly, relevant mass/volume based PBMs have been reported [7, 29, 36, 37], such as the coupling a PBE with a SCM [30], which demonstrated the computational intensive nature of the PBM-SCM description.…”
Section: Introductionmentioning
confidence: 99%
“…Later, more complex formulations were reported using age and an additional intracellular property (e.g. product, RNA) [34, 35]. Similarly, relevant mass/volume based PBMs have been reported [7, 29, 36, 37], such as the coupling a PBE with a SCM [30], which demonstrated the computational intensive nature of the PBM-SCM description.…”
Section: Introductionmentioning
confidence: 99%
“…The cells in different stages of cell cycle have different properties with respect to their size, gene expression, metabolic rates, and shear sensitivity (17, 18). For hybridoma cells, nongrowth or stressed conditions often give increased specific production rates and there appears to be an inverse relation between growth rate and specific MAb productivity (16, 18–20). It has been reported that cultures with slow growth rates or under growth arrest usually have a large portion of the cell population in the G1 phase (21, 22).…”
Section: Introductionmentioning
confidence: 99%
“…When validated, the model can be used to predict in silico the effects of external signals on expression of the gene studied under nonexperimentally tested conditions. The use of mathematical models based on differential equations to describe and predict the behavior of cellular processes is becoming widespread (4,6,8,9,13,20,27). According to previous studies with E. coli, a steady state can be achieved within 5 reactor residence times (12,23,24), which equals 33 h at a dilution rate of 0.15 h Zhulin et al (30) and coincided with generation of a maximal proton motive force.…”
Section: Discussionmentioning
confidence: 99%